PENGEMBANGAN INOVASI PRODUKSI TENUN UNGGAN MENGGUNAKAN DESAIN MOTIF TENUN UNTUK MENINGKATKAN KAPASITAS PRODUKSI USAHA LANSEK MANIH DI KABUPATEN SIJUNJUNG - Lita, Ratni Prima; Rahmadya, Budi; Komalasari, Sanda Patrisia; Elsandra, Yesi; Harits, Muhammad Dzakwan El; Khotimah, Husnul (LPPM Universitas Andalas, 2024)
Unggan weaving is a superior product of Sijunjung Regency and is a priority in the Sijunjung Regency Industrial Development Plan. The aim of the activity is to develop the ability to design Unggan weaving motifs digitally and optimize Unggan weaving production. The method used is a training and mentoring method with quantitative measurement of the success of activities. The activity stages begin with the preparation stage and continue with the implementation stage, namely with motif design training and production assistance to increase product capacity. Every activity is monitored and evaluated to see the success of the activity. The result of the training activities was that 10 craftsmen were trained in designing. The activities carried out are able to increase the ability of entrepreneurs/craftsmen to design motifs digitally, so that the motifs created become more varied with attractive color combinations. The availability of new non-machine looms (ATBM) will increase production capacity. Activities are also able to increase production with the availability of yarn spinning equipment, which will streamline raw material acquisition costs and reduce dependence on raw material suppliers. This activity will continue until 2025 to 2026, so it could have an impact on partners' business performance. The obstacles faced by craftsmen are limited to getting used to designing digitally and needing further training and assistance. From the activities carried out, it can be concluded that craftsmen are able to design digitally and increase production capacity. Craftsmen are expected to use yarn spinning equipment and this could become a new business activity, namely providing yarn spun at CV. Lansek Manih at a cheaper price than yarn suppliers from Silungkang or Bukittinggi.